2003
DOI: 10.1091/mbc.e02-10-0640
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of a Glycosylphosphatidylinositol-anchored Protein via Clathrin-coated Vesicles, Sorting by Default in Endosomes, and Exocytosis via RAB11-positive Carriers

Abstract: Recently, proteins linked to glycosylphosphatidylinositol (GPI) residues have received considerable attention both for their association with lipid microdomains and for their specific transport between cellular membranes. Basic features of trafficking of GPI-anchored proteins or glycolipids may be explored in flagellated protozoan parasites, which offer the advantage that their surface is dominated by these components. In Trypanosoma brucei, the GPI-anchored variant surface glycoprotein (VSG) is efficiently so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
186
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(197 citation statements)
references
References 51 publications
10
186
1
Order By: Relevance
“…No ultrastructural evidence for dynamin collars on CCVs or pits has been obtained (55), and the finding that ConA endocytosis is unaltered by TbDLP suppression is consistent with this hypothesis. Hence, it appears that the original role of dynamin family proteins was in mitochondrial and chloroplast membrane scission, and that the endocytic and exocytic functions for dynamin have arisen later in evolution.…”
Section: Discussionmentioning
confidence: 75%
“…No ultrastructural evidence for dynamin collars on CCVs or pits has been obtained (55), and the finding that ConA endocytosis is unaltered by TbDLP suppression is consistent with this hypothesis. Hence, it appears that the original role of dynamin family proteins was in mitochondrial and chloroplast membrane scission, and that the endocytic and exocytic functions for dynamin have arisen later in evolution.…”
Section: Discussionmentioning
confidence: 75%
“…on VSG trafficking, which have shown that the total VSG complement on the surface of T. brucei is internalized at enormous rate, resulting in a turnover time of 12 min (12,35,43). The fact that it takes more than an hour for the Tf-R to disappear from the surface after the addition of bovine Tf (Fig.…”
Section: Fig 7 Variation Of Tf-r Levels In T Brucei Growing In Culmentioning
confidence: 99%
“…This is unexpected, as trypanosomes are normally able to handle the routing of new VSG efficiently. The Tf-R resembles a VSG dimer in structure and in its glycosylphosphatidylinositol anchor (23), but T. brucei makes at least 100-fold more VSG than Tf-R, and only 11% of this VSG is present intracellularly (12,35,43).…”
Section: Fig 7 Variation Of Tf-r Levels In T Brucei Growing In Culmentioning
confidence: 99%
“…This region is characterized by a narrowing of the FP at its apical end until it is little larger in diameter than the flagellum. Again, the cytoskeleton appears central to this: in particular, an electron-dense structure called the ''collar'' can be seen on the cytoplasmic side of this region, and ablation of a protein that localizes to this structure disrupts FP morphogenesis (7).Because of its central importance to pathogenicity, the endocytic activity of T. brucei has long been studied by using well-defined markers for endocytosis and subcellular compartments (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These studies have established the speed, timing, and routes of uptake and traffic within the cell (1,16,18,20), but a number of critical questions remain unanswered.…”
mentioning
confidence: 99%
“…These studies have established the speed, timing, and routes of uptake and traffic within the cell (1,16,18,20), but a number of critical questions remain unanswered. First, given the constriction of the FP at its junction with the cell body membrane, how do molecules in the extracellular milieu gain access to its lumen?…”
mentioning
confidence: 99%